From heresy to liberty: The political trajectory of Unitarian theology and its contemporary relevance - Gilbert Timothy Majesty; Demsy Jura; Dirk Roy Kolibu (KAMASEAN: Jurnal Teologi Kristen, 2025)
This study analyzes the political trajectory of Unitarian theology from heresy to liberty and its contemporary relevance. Employing a qualitative descriptive analysis method, the findings reveal: The Origin and Development of Unitarianism, tracing its roots from early anti-Trinitarian thought (such as Arianism) to its crystallization during the Reformation through figures like Michael Servetus, and its evolution into a liberal movement in America. The Theological and Political Conflict with Trinitarianism is multidimensional; the rejection of the Trinity was perceived as a challenge to both ecclesiastical and state authority, inciting persecution and influencing political stability. Religious Freedom in the Modern Era demonstrates a paradigm shift: from a persecuted minority, Unitarianism became an architect of religious freedom thought and the separation of church and state, particularly within the Enlightenment and American constitutional contexts. The Socio-Political Implications of its doctrine are significant, fostering democracy, pluralism, social justice, and rational education. The response of the Orthodox or Catholic Church consistently rejects Unitarianism as a modern form of Arianism that threatens orthodoxy and social order. The study concludes that Unitarianism’s journey is not merely a theological evolution but a dynamic reflection of the dialectic among religious belief, political power, and civil liberty in Western history, while also offering a critical lens for understanding challenges to religious freedom in states with institutionalized theological orthodoxy.